Developing and Validating a Brief Jail Mental Health Screen in Maryland and New York, 2005-2006 - Steadman, Henry J. ([Verlag nicht ermittelbar], 2008)
The goal of this research project was to develop an efficient mental health screen that would aid in the early identification of severe mental illnesses and other acute psychiatric problems during the jail intake process. The researchers sought to validate the Brief Jail Mental Health Screen (BJMHS) as such a tool. Participants in the study included male and female jail detainees admitted to one of four county jails, two in Maryland and two in New York, from November 2005 to June 2006. A total of 10,562 jail detainees were screened using the BJMHS-R (Part 1). The screening data were used to identify a sub-sample of detainees who were systematically sampled for a detailed clinical assessment, the Structured Clinical Interview for DSM-IV (SCID), which was conducted by a trained research interviewer in order to validate the screen. A subset of 464 jail detainees completed the SCID interviews (Part 2). Part 1, Tracking Data, contains 54 variables, including items and scores from the BJMHS-R, that were used to used to identify and generate a list of potential detainee participants for the SCID interview. Part 2, Interview Data, contains 326 variables, including items and scores from both the BJMHS-R and the SCID interviews, that were used to validate the screen.